2020
DOI: 10.1126/scitranslmed.abb7028
|View full text |Cite
|
Sign up to set email alerts
|

Long-term skin-resident memory T cells proliferate in situ and are involved in human graft-versus-host disease

Abstract: The skin contains a population of tissue-resident memory T cells (Trm) that is thought to contribute to local tissue homeostasis and protection against environmental injuries. Although information about the regulation, survival program, and pathophysiological roles of Trm has been obtained from murine studies, little is known about the biology of human cutaneous Trm. Here, we showed that host-derived CD69+ αβ memory T cell clones in the epidermis and dermis remain stable and functionally competent for at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(112 citation statements)
references
References 87 publications
(94 reference statements)
9
92
0
6
Order By: Relevance
“…As hypoxia and TGF-β are common features of the tumor microenvironment (TME), our results suggest they may contribute to CD103 + TIL generation in vivo. Additionally, our results may help explain recent observations that TIL RM are more radioresistant, as hypoxia and TGF-β are known to contribute to radioresistance, and DEGs in radioresistant human skin T RM show enrichment in the hypoxia pathway, relative to tissue-infiltrating T cells ( 40 , 46 48 ).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…As hypoxia and TGF-β are common features of the tumor microenvironment (TME), our results suggest they may contribute to CD103 + TIL generation in vivo. Additionally, our results may help explain recent observations that TIL RM are more radioresistant, as hypoxia and TGF-β are known to contribute to radioresistance, and DEGs in radioresistant human skin T RM show enrichment in the hypoxia pathway, relative to tissue-infiltrating T cells ( 40 , 46 48 ).…”
Section: Resultssupporting
confidence: 69%
“…Importantly, NR3C1 has previously been shown to promote the formation of memory precursor T cells and can be upregulated by hypoxia ( 38 , 39 ). In addition, there was considerable overlap between the transcriptional profiles of our i-T RM and human skin T RM , including a number of canonical hypoxia-responsive genes (e.g., LDHA , MMP9 , CA9 ), as well as LGALS3 , a newly identified marker of human skin T RM ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…Pretransplant conditioning which typically consists of chemoimmunotherapeutic drugs and/or total body irradiation were thought to eliminate host T cells and therefore not play a role in GVHD, but new studies indicate that host T cells resident in peripheral tissues are highly resistant to depletion, even after high-intensity conditioning (109). In humans, host-derived Trm cells have been found in patients' skin lesions before and after allo-HCT and showed distinct transcriptomic program with RUNX3 and galectin-3 as the phenotypic signatures for these cells as compared to blood T cells (110). Similarly, host T cells were found in all skin and colon from patients with aGVHD after allo-HCT.…”
Section: Trmmentioning
confidence: 99%
“…Human IL-26 could attenuate immune responses in a mouse model of acute colitis. Next, Strobl J et al used single-cell technique to study tissue-resident memory T cells in skin, and they identified RUNX3 and LGALS3 as new markers for this type of T cells (74). They also identified a large number of host-derived tissue-resident memory T cells in skin lesions from patients developing graft-versus-host disease, suggesting the potential contribution of these cells to this disease.…”
Section: T-cell Biology In Autoimmunitymentioning
confidence: 99%